Tantangan Profesi Akuntan di Era Revolusi 4.0 pada Siswa/i SMKN 7 Medan - Rifdah Riyan Dara; Sovia Lolita Apriani Pardede; Corinna Wongsosudono; Ripka Seriidahna Ginting; Fajrillah Fajrillah; Pratiwi Putri Lestari (Insight Power (Kekuatan Wawasan), 2022)
The era of the industrial revolution 4.0 poses a challenge to society and the government with an increasing number of old manual jobs that will disappear and be replaced by the use of advanced technology in the form of machines, robots and others. Unpreparedness and inability of human resources to adapt and use technology can cause unemployment in the future. The information gap related to workforce needs can be overcome by introducing a new literacy model consisting of technological literacy, digital literacy and human literacy. Efforts to increase this new literacy are carried out by holding community service activities. The implementation of this community service in collaboration with SMK Negeri 7 Medan Amplas with participants consisting of school students, the number of participants who took part in this community service activity was 15 people. This activity was held aiming to provide students with increased insight related to the industrial revolution 4.0, especially big data and data mining so that they can prepare themselves earlier to enter the world of work in the era of the industrial revolution 4.0. Submission of material is done by lecture and question and answer. The results of this community service activity showed thatKeywords: industrial revolution 4.0, digital literacy, human literacy, big data, data mining